Personality characteristics and its effect on performance in the race BMX - Hrebickova, S.; Pacholik, V.; Mach, J.; Labounková, R. (Journal of Human Sport & Exercise, 2014)
The aim of this study was to describe personality characteristics of top athletes - 10 elite bicross (BMX) racers (18+ years), both men and women. For our research we used SPARO test - monitoring of basal psychical autoregulation of personality, which was evaluated with t-test. Particular segments were compared with population and with top athletes of different sports. BMX racers had significantly higher (p < 0.05) intensity of autostimulation, airiness (-5.92±2.54), searching for emotional experiences (3.4 ±2.35) and higher willingness to risk (6,54±2,37). Simultaneously it confirmed higher anxiety (3.35±3,2.1), need of independence (3,73±2.00) and dominant need of experiential attitude (-2,55±2,38). Results show characteristics of BMX racers, which correspond with characteristic of this cycling discipline, and also show personality attributes which are important for success in this sport. - See more at: http://www.jhse.ua.es/jhse/article/view/768#sthash.A0RrhtuX.dpuf